The Annual Convention of the Association of Muslim Social scientists - M. A. Muqtedar Khan (International Institute of Islamic Thought, 1999)
The Annual Convention of the Association of Muslim Social Scientists (AMSS), was held at the Graduate School of Islamic and Social Sciences in Leesburg, VA 29-31 October. By all accounts, this convention was a success and heralds a resurgence of the Association. The convention generated an air of excitement and expectations about the Association’s immediate future. Over 150 participants attended and 70 presentations were made. In addition, the convention was graced by nine foreign scholars: two from India, one from Brunei, one from Malaysia, three from Canada, one from France, and one from Turkey. The Faruqi memorial lecture was delivered by AbdulHameed AbuSulayman, the president of the International Institute of Islamic Thought (IIlT). He focused on the Muslim communities’ need to focus on the intellectual development of children because it is an important aspect of the revival of the ummah. The keynote address at the banquet was given by Tariq Ramadan a prominent Muslim social scientist and community leader from France. His talk brought a Efreshing focus to what it means to be an engaged Western Muslim. In many ways this convention was a turning point in the history of AMSS. Here, the old and the new met and had a meaningfid dialogue about the direction of the Association. The convention also marked a change of guard as many new and younger Muslim scholars, particularly graduate students, joined the board. Faizan Haq, a B.D. student at SUNY Buffalo was elected general secretary and is also in charge of the AMSS outreach ...